DETERMINAN MINAT MAHASISWA UIN RADEN MAS SAID SURAKARTA MENGGUNAKAN BRIMO - Heri Catur Fredi Utomo; Reyhan Ramzy Rudi Pratama (Jurnal Ekonomi Sakti, 2023)
The Purpose of this study is examining the impact of the benefits of convenience, usability, accessibility and service on the interest of UIN Raden Mas Said Surakarta students by using BRIMO. The result of this research of UIN Raden Mas Said Surakarta students by using BRImo. The Amount of sample were 107 respondents. In this reseach using the test method of validity , reliability, classic assumption and analysis of multiple regression. The Calculation of data using SPSS software version 23. The research method used quantitative and the technology acceptance of model (TAM) theory with 5 variables, namely the variables of convenience, usability, accessibility, usefulness and interest in service. The results of this research were variables have no significant effect, namely the expediency variable, while the variables of convenience, usability, access ability and service had a significant effect on the variable of interest. The results of this research showed that the variables of convenience, usability and accessibility have a significant effect to the intention by using BRIMO, while the utility variable did not affect the intention by using BRIMO. Keywords: convenience, usability, accessibility, benefits and interest